2012
DOI: 10.2147/opth.s36261
|View full text |Cite
|
Sign up to set email alerts
|

Severe ocular hypertension secondary to systemic corticosteroid treatment in a child with nephrotic syndrome

Abstract: PurposeTo report a case of severe, acute ocular hypertension in a 6-year-old child, 7 days after initiating treatment with oral prednisolone, due to nephrotic syndrome.MethodsA 6-year-old female Caucasian child was diagnosed with nephrotic syndrome and treated with oral prednisolone (60 mg/day). Seven days later the child initiated complaints of headache, vomiting, ocular pain, and photophobia. Ophthalmologic examination revealed a severely increased intraocular pressure (IOP) of 52 mmHg in the right eye and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…The precise mechanism of SIG is unclear, but it is assumed to involve mainly trabecular meshwork oedema and increased resistance to aqueous humour drainage. 4 The few studies of SIG in children 19,20 found that they were particularly susceptible, [21][22][23][24][25] exhibiting more severe optic nerve damage with earlier onset and more rapid progression than adults. 7 Notably, increased IOP and glaucoma may occur many years after initiation of GC therapy and have been reported as delayed complications in survivors of childhood cancer.…”
Section: Steroid-induced Oht and Glaucoma In Childrenmentioning
confidence: 99%
“…The precise mechanism of SIG is unclear, but it is assumed to involve mainly trabecular meshwork oedema and increased resistance to aqueous humour drainage. 4 The few studies of SIG in children 19,20 found that they were particularly susceptible, [21][22][23][24][25] exhibiting more severe optic nerve damage with earlier onset and more rapid progression than adults. 7 Notably, increased IOP and glaucoma may occur many years after initiation of GC therapy and have been reported as delayed complications in survivors of childhood cancer.…”
Section: Steroid-induced Oht and Glaucoma In Childrenmentioning
confidence: 99%
“…Visual disturbances also translate into a significant socioeconomic burden on family and society due to increased resources needed to raise a visually impaired child [ 9 ]. Early detection and prompt management of the side effects can prevent visual deprivation and eventual amblyopia due to cataracts as well as permanent blindness in cases of optic nerve damage in steroid induced glaucoma [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all patients described returned to an IOP within normal range after discontinuation of the glucocorticoid alone; only one patient needed IOP-lowering eyedrops. In addition to these examples, multiple other case reports and case series on the subject have been published [ 48 , 49 , 50 , 51 ]. These reports suggest the need for clear clinical guidance regarding the ophthalmological follow-up of glucocorticoid users.…”
Section: Discussionmentioning
confidence: 99%